Primary Non-Hodgkin’s lymphoma of epidural space- A case report of great mimicker and review of literature (Indian Journal of Case Reports, 2019)
Primary Non-Hodgkin’s lymphoma of epidural space is a rare entity. Clinical presentation and imaging studies were bizarre and posed the difficulty in diagnosis. Since the management protocol of spinal lymphoma is yet to be standardized, so the prognosis is still looming. Here we are reporting a case of epidural primary Non-Hodgkin’s lymphoma in young adult female, who presented with backache and weakness.